Intradural Extramedullary Vascular Schwannoma at Upper Dorsal LevelA Case Report - Farazi, Md. Mohsin Ali; Saha, Sukumar; Sarder, Anirudho; Iqbal, Rabiul (Medicine Today, 2012)
A young male patient of 24 years was presented with the complaints of upper back pain, hyposthesia and unable to walk. MRI of upper dorsal region reveals intradural extramedullary mass lesion extending from D1 to D4 with moderate enhancement of gadolinium. Hence an extensive laminectomy and total removal of the mass. Peroperative impression and histopathological findings confirm vascular schwannoma. After operation dramatic improvement of signs and symptoms, patient can walk with minimum support during discharge from hospital. Medicine Today 2010 Volume 22 Number 02 Page 103-105 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12445